2022
DOI: 10.1021/acs.jafc.2c05939
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA Profiling Reveals an Abundant circBDP1 that Regulates Bovine Fat Development by Sponging miR-181b/miR-204 Targeting Sirt1/TRARG1

Abstract: The proliferation and differentiation of preadipocytes is an important factor determining bovine fat development, which is closely related to the feed conversion ratio, carcass traits, and beef quality. The purpose of this study was to identify the effects of candidate circRNA and miRNA on the proliferation and differentiation of bovine preadipocytes in order to provide basic materials for molecular breeding in cattle. circRNA sequencing was performed on bovine adipocyte samples at different differentiation ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The ceRNA (competing endogenous RNAs) hypothesis has revealed a new mechanism for endogenous interactions between Rnas. Relevant studies have been conducted in cattle ( 50 ), goats ( 33 ) and pigs ( 51 ). circBDP1 can regulate the proliferation and differentiation of bovine adipose cells through the mir-204 / TRARG1 pathway ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ceRNA (competing endogenous RNAs) hypothesis has revealed a new mechanism for endogenous interactions between Rnas. Relevant studies have been conducted in cattle ( 50 ), goats ( 33 ) and pigs ( 51 ). circBDP1 can regulate the proliferation and differentiation of bovine adipose cells through the mir-204 / TRARG1 pathway ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Relevant studies have been conducted in cattle ( 50 ), goats ( 33 ) and pigs ( 51 ). circBDP1 can regulate the proliferation and differentiation of bovine adipose cells through the mir-204 / TRARG1 pathway ( 50 ). circTUT7 influences the development process of porcine embryonic muscle by regulating the expression of HMG20B in the ceRNA mechanism ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…In adipose tissues from cachectic patients, circPTK2 competitively binding to miR-182-5p then promoted lipolysis and lipogenesis were inhibitied [ 46 ]. Based on circRNA-seq analysis, circBDP1 was proved to regulate bovine fat development by sponging miR-181b/miR-204 targeting Sirt1/TRARG [ 47 ]. In this study, we using miRanda and TargetFinder softwares predicting the miRNA binding sites for these DE-circRNA and a circRNA-miRNA interaction network for the DE-circRNAs was constructed by using Cytoscape software.…”
Section: Discussionmentioning
confidence: 99%
“…Novel circPPARA has been proven to promote differentiation and inhibit the proliferation of porcine intramuscular preadipocytes [ 105 ]. Another work identified that circBDP1 accelerated the proliferation and differentiation of bovine preadipocytes [ 112 ]. An increasing number of studies have revealed adipogenesis- and development-related circRNAs ( Supplementary Table S3 ).…”
Section: Circrnas and Adipogenesismentioning
confidence: 99%